2019
DOI: 10.1021/acsnano.8b09270
|View full text |Cite
|
Sign up to set email alerts
|

An Upconversion Nanoparticle Enables Near Infrared-Optogenetic Manipulation of the Caenorhabditis elegans Motor Circuit

Abstract: Near-infrared (NIR) light penetrates tissue deeply, but its application to motor behavior stimulation has been limited by the lack of known genetic NIR light-responsive sensors. We designed and synthesized a Yb 3+ /Er 3+ /Ca 2+ -based lanthanide-doped upconversion nanoparticle (UCNP) that effectively converts 808 nm NIR light to green light emission. This UCNP is compatible with Chrimson, a cation channel activated by green light; as such, it can be used in the optogenetic manipulation of the motor behaviors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…To assess whether the UCNPs potentiate cell killing by simultaneously activating both miniSOG and Chrimson under NIR light, we choose C. elegans DVC neuron as an exemplary neuron to perform the experiments, in view that it is a single, unilateral excitatory glutamatergic interneuron that regulates the backward locomotion 8a,16. With representative tail localization of the DVC soma in dorsorectal ganglion, a long ventral neurite outgrows from soma to the nerve ring (NR) in the head ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether the UCNPs potentiate cell killing by simultaneously activating both miniSOG and Chrimson under NIR light, we choose C. elegans DVC neuron as an exemplary neuron to perform the experiments, in view that it is a single, unilateral excitatory glutamatergic interneuron that regulates the backward locomotion 8a,16. With representative tail localization of the DVC soma in dorsorectal ganglion, a long ventral neurite outgrows from soma to the nerve ring (NR) in the head ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanide‐doped upconversion nanoparticles (UCNPs) have gained significant research interests in optogenetics due to their capability of converting tissue‐penetrable near‐infrared (NIR) light into programmable ultraviolet (UV) to NIR emissions . By carefully modulation of lanthanide nanoarchitecture and precisely selection of lanthanide dopants, their emissions can be finely tuned to match the working spectrum of established optogenetic light‐sensitive proteins, such as miniSOG (excited at ≈470 nm), NpHR (excited at ≈590 nm), or Chrimson (excited at ≈610 nm) 8a,b,d,g,9. Consequently, when coupled with UCNPs, neuron activities can be indirectly regulated by NIR irradiation and to control the locomotion behavior in C. elegans or mice 8a,d,f.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 In another recent study, Yb 3þ ∕Er 3þ ∕Ca 2þ -based lanthanide-doped UCNP has been shown to effectively activate Chrimson-expressing, inhibitory GABAergic motor neurons, leading to a reduced action potential firing in the body wall muscle of C. elegans and resulting in locomotion inhibition. 58 This UCNP provides a useful integrated optogenetic toolset for wide applications, as it exhibits negligible toxicity in neural development, growth, and reproduction, along with the nonactivation of the animal's temperature response with the NIR energy required to elicit behavioral and physiological responses. Using it with vf-Chrimson may lead to better NIR optogenetic manipulation of motor circuits in various organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In another interesting study, Ao and colleagues studied the movement behavior control of Caenorhabditis elegan by Yb 3+ /Er 3+ /Ca 2+ ‐based lanthanide‐doped UCNPs. [ 134 ] They found that the uranium‐doped UCNP effectively activated Chrimson (a green‐activated cation channel) and inhibited GABAergic motor neurons during 808 nm NIR light irradiation, thereby reducing the action potential of body wall muscle discharge and inhibiting the movement of nematodes. Thanks to the deep penetration of NIR‐Ⅱ light (1000–1700 nm), UCNP‐mediated optogenetics have also been used to spur deep brain neurons in living animals.…”
Section: Advanced Nir Light For Spatiotemporal Modulation Of Cell Funmentioning
confidence: 99%